2010
DOI: 10.1126/scitranslmed.3001304
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Early Physiological Responses Predicts Later Illness Severity in Preterm Infants

Abstract: Physiological data are routinely recorded in intensive care, but their use for rapid assessment of illness severity or long-term morbidity prediction has been limited. We developed a physiological assessment score for preterm newborns, akin to an electronic Apgar score, based on standard signals recorded noninvasively on ad- mission to a neonatal intensive care unit. We were able to accurately and reliably estimate the probability of an individual preterm infant’s risk of severe morbidity on the basis of nonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
128
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(133 citation statements)
references
References 29 publications
4
128
0
1
Order By: Relevance
“…Although these illness severity scores are likely to be high in infants with early-onset sepsis and shock in the first day after birth, they have not been shown to predict later development of sepsis or NEC. A score incorporating gestational age, birth weight, and mean and standard deviation of heart rate, respiratory rate, and oxygen saturations in the first 3 h after birth was reported to be significantly associated with development of late-onset sepsis in a study of 138 preterm infants [17]. Low heart rate variability in the first week after birth was also found to be associated with development of NEC in a study of 70 preterm infants [18].…”
Section: Risk Assessment For Sepsis and Necmentioning
confidence: 95%
“…Although these illness severity scores are likely to be high in infants with early-onset sepsis and shock in the first day after birth, they have not been shown to predict later development of sepsis or NEC. A score incorporating gestational age, birth weight, and mean and standard deviation of heart rate, respiratory rate, and oxygen saturations in the first 3 h after birth was reported to be significantly associated with development of late-onset sepsis in a study of 138 preterm infants [17]. Low heart rate variability in the first week after birth was also found to be associated with development of NEC in a study of 70 preterm infants [18].…”
Section: Risk Assessment For Sepsis and Necmentioning
confidence: 95%
“…Quantitative analysis of multiple risk factors combined in a multivariate model can improve outcome prediction (7). Saria et al (9) showed that a combination of quantitative features of early physiological measurements, including heart rate (HR), respiratory rate (RR), and peripheral oxygen saturation (SpO 2 ), could predict short-term outcome with a high level of accuracy (sensitivity of 86% and specificity of 96%). The absence of a reliable measure of neurological function, however, may limit the ability of these approaches to predict neurodevelopment in the longer term, beyond the early intensive care stage.…”
mentioning
confidence: 99%
“…The multimodal model combines EEG grading with quantitative features of routinely-available physiological signals, namely SpO 2 and HR (9). A clinical course score, which represents a best estimate of long-term outcome from clinical history of the intensive care period, is used to compare performance of this multimodal approach.…”
mentioning
confidence: 99%
“…Иными словами, области трансляционной биоин-форматики отведена роль «мостика» между знаниями фундаментальных исследователей и врачей-клини-цистов, чтобы «принести инновации с лабораторно-го стола к постели пациента» («link innovations from bench to bedside») [51,52]. В частности, в Госпитале для больных детей (The Hospital for Sick Children) в Торонто (Канада) был осуществлен пилотный проект анализа жизненных показателей в режиме реального времени [53], а в другой работе было про-демонстрировано, что паттерны данных жизненных показателей могут помочь прогнозировать как кратко-срочную, так и долгосрочную заболеваемость у недо-ношенных детей [54].…”
Section: персонализированная педиатрияunclassified